If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(0.6667x + -4) = 14 Reorder the terms: -3(-4 + 0.6667x) = 14 (-4 * -3 + 0.6667x * -3) = 14 (12 + -2.0001x) = 14 Solving 12 + -2.0001x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2.0001x = 14 + -12 Combine like terms: 12 + -12 = 0 0 + -2.0001x = 14 + -12 -2.0001x = 14 + -12 Combine like terms: 14 + -12 = 2 -2.0001x = 2 Divide each side by '-2.0001'. x = -0.9999500025 Simplifying x = -0.9999500025
| -7x-8x=60 | | 20-x/2=10 | | 4+9j-8+8+7j+94= | | 5z-9z=20 | | 0.4x-0.5(2x-1)=-0.3(x+4) | | 17-6n=-49 | | 156=n^2+n | | (2x+3y+1)dx+(4x+6y-5)dy=0 | | -3(2/3x-4)=14 | | Y-3=3(x+9) | | (2x+3y+1)dx+(4x+6y-5)=0 | | 4c-6-3x=2+5x | | x/5=0.41 | | 11X=9X+46 | | Y+6=-5(x+9) | | Y+2=-6(x-7) | | 3z^2+10z+3=0 | | 6x^2+x-75=0 | | -40=-(4v-4)-2(6-6v) | | Y+1=-7(x+2) | | 2+2y+-3=11 | | (2x+3y+1)dx=-(4x+6y-5)dy | | 11v+14x=3450 | | x+2.1x=-26.4 | | y-45+6x=0 | | 16=s/2 | | -2(2x+3)=18 | | -16=4(-v-6)-3(4-8v) | | 6x-3=k(-2x+1) | | 24=-4(1-7n)+7(n+4) | | -4(5x-7)=168 | | 8k+54=-14 |